2021
DOI: 10.1186/s43008-021-00068-w
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling hybridization in Phytophthora using phylogenomics and genome size estimation

Abstract: The genus Phytophthora comprises many economically and ecologically important plant pathogens. Hybrid species have previously been identified in at least six of the 12 phylogenetic clades. These hybrids can potentially infect a wider host range and display enhanced vigour compared to their progenitors. Phytophthora hybrids therefore pose a serious threat to agriculture as well as to natural ecosystems. Early and correct identification of hybrids is therefore essential for adequate plant protection but this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 134 publications
(201 reference statements)
1
40
0
Order By: Relevance
“…Above all, the major Phytophthora clades are still confirmed to be a relatively tight, bush-like, fundamentally monophyletic, evolutionary cluster. Indeed Clades 9 and 10, considered by Cooke et al ( 2000 ) to be more distant, are now more closely aligned with the other major clades (Jung et al 2017c ; Yang et al 2017 ; Scanu et al 2021 ; Van Poucke et al 2021 ; Chen et al 2022 ). This is in contrast to the oomycete genus Pythium which, beginning with Cooke et al ( 2000 ), has been shown to be evolutionarily divergent and polyphyletic, and in consequence was split into several monophyletic genera (de Cock et al 2015 ; Uzuhashi et al 2010 ).…”
Section: Commentarymentioning
confidence: 90%
See 4 more Smart Citations
“…Above all, the major Phytophthora clades are still confirmed to be a relatively tight, bush-like, fundamentally monophyletic, evolutionary cluster. Indeed Clades 9 and 10, considered by Cooke et al ( 2000 ) to be more distant, are now more closely aligned with the other major clades (Jung et al 2017c ; Yang et al 2017 ; Scanu et al 2021 ; Van Poucke et al 2021 ; Chen et al 2022 ). This is in contrast to the oomycete genus Pythium which, beginning with Cooke et al ( 2000 ), has been shown to be evolutionarily divergent and polyphyletic, and in consequence was split into several monophyletic genera (de Cock et al 2015 ; Uzuhashi et al 2010 ).…”
Section: Commentarymentioning
confidence: 90%
“…Clade structure sustained Göker et al ( 2007 ) 2009 400–600 Phytophthora species predicted Brasier ( 2009 ) 2014 Divergence of Phytophthora Clades predicted at 19.8–39 m years ago Matari and Blair ( 2014 ) 2017 Designation of Nothophytophthora gen. nov. Phytophthora origin pre the Gondwana-Laurasia separation (> 180 Myr) proposed Jung et al ( 2017a ) 2018 Multiple evolution of downy mildews from Phytophthoras demonstrated Bourret et al ( 2018 ) 2021 First phylogeny from genome-wide sequencing. Clade structure sustained Van Poucke et al ( 2021 ) 2021 Phytophthora reaches 200 described species Scanu et al ( 2021 ), Chen et al ( 2022 ) …”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations